Evaluation of Organophosphates Residue in Stored Cereals from Some Selected Markets in Jalingo, Nigeria - Tutuwa, Jummai Adamu; David, Bando Christopher; Tadawu, Rejoice Habila; Nuhu, Imbasire; Sunday, Oche Gabriel; Ogu, Emmanuel Odiba; Haruna, Peace Gambo; Jesse, Polly Shingu (Darul Yasin Al Sys, 2024)
Cereal grains such rice, sorghum, maize and millet among others are the staple foods in large parts of the world, supplying most of the energy and bulk in diets. Pesticide residue analysis in cereals from the various sampling locations for this dissertation revealed the following organophosphate pesticide residue were present in cereals analyzed Dichlorvos, Diazinon, Phorate sulfon, Malathion, Phorate, Chloropyrifos, Methyl Parathion, Profenofos, Ethion, Dimethoate, Phorate Sulfoxide, Phosalone, Edifenfos, Fenitrothion and Chlorofenvinfos. The presence of pesticide residues is detected in the samples of cereals (Rice, Maize, Millet and sorghum) analyzed. This could be as a result of high utilization of various pesticides during plant, cultivation and storage thus leading to the bioaccumulation of this substance in the individual cereals. It indicates high levels of non-carcinogenic risk associated with the life time consumption of cereals produce and sold within this region. Based on findings from this study’s, I hereby make the following recommendations. Regulatory agencies in Nigeria should step up efforts to ensure compliance with the ban on these chemicals. Farmers and other pesticide users also need to be educated on the dangers of using banned products and on the over application of these pesticides. Furthermore, farmers should be educated on the properly usage of these chemical product, during plant, harvest and storage. Also, manufacturers of these chemicals should produce less toxic pesticide using organic materials in other to prevent the health risk associated with chemical pesticide and their residues in food crops and the environment.